2011
DOI: 10.4236/eng.2011.34039
|View full text |Cite
|
Sign up to set email alerts
|

Electrowinning of Copper Using Rotating Cylinder Electrode Utilizing Lead Anode

Abstract: The effect of lead anode, rotating cylinder electrode (RCE), amount of 1, 2-dihydroxypropane (12-DHP), temperature and rotation on the electrowinning of copper from low concentration acidified copper sulphate solution has been investigated. Copper powder was electrodeposited onto RCE that made of pure copper. From cyclic voltammetry experiments, an empirical parameter called the departure percent, S, was obtained which may represent the stability of the organic additive in the given medium and under the experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…in the literature, mechanical improvements to the electrolytic synthesis of copper powders, such as an electrode from a rotating disk or cylinder, have also been proposed [23][24][25][26]. in this version of the process, the cathode in cylindrical shape rotates, partially immersed in the electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…in the literature, mechanical improvements to the electrolytic synthesis of copper powders, such as an electrode from a rotating disk or cylinder, have also been proposed [23][24][25][26]. in this version of the process, the cathode in cylindrical shape rotates, partially immersed in the electrolyte.…”
Section: Introductionmentioning
confidence: 99%
“…Using an experimental procedure, Soliman et al (2011) obtained Sherwood number to calculate mass transfer in an electrowinning cell with rotating cylinder electrodes. Using analytical and experimental studies, Coleman (Coleman and Roy 2014) exposed a specific test cell with a small electrode interval to ultrasonic waves, obtained its mass transfer relationships, and showed that the use of ultrasonic waves would increase the mass transfer in the cell.…”
Section: Introductionmentioning
confidence: 99%
“…According to physical and chemical laws (Equation 1), the limiting current density is bound up with mass transport of Cu 2+ [9] and the limiting current density is inversely related to the diffusion boundary layer. Therefore, the limiting current density may be raised obviously by decreasing diffusion boundary layer thickness, which could be achieved by electrolyte agitation [10] , rotation of cathode [11] and enhanced flow at cathode [7,12] .…”
Section: Introductionmentioning
confidence: 99%